Employees health and retirement retirement for example Voivodeship Specialist Hospital M. University in Lodz - Timler, Dariusz; Szarpak, Łukasz; Madziała, Marcin; Kałuża-Kopias, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The aim of the paper was to analyzed the population of employees of Copernicus Memorial Hospital of Lodz in the group of 60+ (for women) and 65+ (for men) and the group protected by law from reduction (4 years before retire) as an indicator of staffing needs in short future. Material and methods Present records from human resources of employees of Copernicus Memorial Hospital of Lodz were analyzed (30.04.2012). Total number of employees were 2152 people. 69 of them met criteria of group I, 213 people met criteria of group II. Also there were the group of employees working in hospital over 35 years - group III. We used program Statistica 8.0 edition 0607b-P by StatSoft Polska Sp. z o.o. for statistical analysis. Results The population of group I consist of the group of women (n=56; 81%) and the group of men (n=13; 19%). There were more women than men. Average age of the group I was 65,11 ± 6,32 years old. The group of women was younger than the group of men about 7 years. The group I is 3% of the total number of employees from Copernicus Memorial Hospital of Lodz, Poland. The group II (protected by law from reduction; 4 years before retire) is 10% of the total number of employees from Copernicus Memorial Hospital of Lodz, Poland. The population of group II consist of the group of women (n=183; 86%) and the group of men (n=30; 14%). There were also more women than men. The population of group III consist of the group of women (n=70; 86%) and the group of men (n=11; 14%). The group III is 3,76% of total number of employees from Copernicus Memorial Hospital of Lodz, Poland. Conclusions The analysis of hospital's employees records is a good point to start discern of staff needs. The employment's politic in hospital should be more active. Part-time job is one of the solution especially for people 65+. For sure we need to change our mind about an employee's management. 13% of analyzed population of employees of Copernicus Memorial Hospital of Lodz shows staffing needs but further analysis must be done.